General strategy for tuning the Stokes shifts of near infrared cyanine dyes. Issue 47 (9th November 2020) - Zhang, Jun; Moemeni, Mehdi; Yang, Chenchen; Liang, Fangchun; Peng, Wei-Tao; Levine, Benjamin G.; Lunt, Richard R.; Borhan, Babak
Abstract : A series of amine substituted cyanines show spectral characteristics that are dependent on the structure of the substituted amine, with Stokes shifts that range from 24–180 nm. Computational analysis informs on the ground and excited state structures. Abstract : We report a significant Stokes shift enhancement in near-infrared fluorescing cyanines as a result of C4′-substitution with cyclic or acyclic amines. Based on a combined experimental and density functional study, a simple strategy for optimizing the Stokes shift is proposed. By tuning the relative energies of cyanine-like and bis-dipolar conformers, differing in the rotational angle of the amine substituent, it is possible to develop molecules that undergo conformational change upon excitation, resulting in a predictable Stokes shift.